Prevalence of risk phenotypes associated with CYP2C9*2, *3, and VKORC1 c.-1639G>A genetic polymorphisms in world populations: implications in clinical practice - Biswas, Mohitosh; Murad, Murshadul Alam; Ershadian, Maliheh; Kali, Most. Sumaiya Khatun; Shin Sim, Maw; Ibrahim, Baharudin; Sukasem, Chonlaphat (Frontiers in Pharmacology, 2025)
BackgroundThe safety or efficacy of drugs may be affected by the genetic variability of CYP2C9 or VKORC1. Patients may be at increased risk of drug-related toxicities, for example, bleeding events, if they carry CYP2C9*2 (rs1799853), CYP2C9*3 (rs1057910), or VKORC1 c.-1639G>A (rs9923231) genetic variants.MethodsThe allele frequencies of CYP2C9*2, *3, and VKORC1 c.-1639G>A were obtained from the 1000 Genomes Project Phase III in line with Fort Lauderdale principles. Predictive risk phenotypes and correlations were assigned based on the carrying of characteristic allele carriers following international pharmacogenomics (PGx)-based dosing guidelines.ResultsIntermediate and poor metabolizers were predicted to be risk phenotypes (17.8%; 95% CI 16.3%–19.3%) due to inheriting CYP2C9*2 and *3 genetic variants. These risk phenotypes were highest in European (35%; 95% CI 30.8%–39.2%), followed by South Asian (26.8%; 95% CI 22.9%–30.7%), American (25.9%; 95% CI 21.3%–30.5%), East Asian (6.7%; 95% CI 4.5%–8.9%), and African populations (2.1%; 95% CI 1%–3.2%). In addition, sensitive and highly sensitive responders were considered risk phenotypes (33.1%; 95% CI 31.3%–35%) when combining CYP2C9*2 and *3 variants with VKORC1c.-1639G>A. These risk phenotypes were most prevalent in East Asian (79.6%; 95% CI 76%–83.1%), followed by European (38.6%; 95% CI 34.3%–42.8%), American (30%; 95% CI 25.2%–34.8%), South Asian (25.2%; 95% CI 21.3%–29%), and African populations (1.2%; 95% CI 0.4%–2%), respectively. The prevalence of risk phenotypes in different ethnic groups was statistically significant (p < 0.05; 1.94 × 10−175, χ2 test). According to clinical annotations in the PharmGKB, the safety or efficacy of at least 29 commonly prescribed drugs is impacted by the genetic polymorphisms of CYP2C9/VKORC1 c.-1639G>A to varying degrees. The PGx label information is available for at least 23 drugs, and the Clinical Pharmacogenetics Implementation Consortium (CPIC) has already recommended PGx-based dosing guidelines for at least 11 of these medications, based on the genetic variability of CYP2C9/VKORC1 c.-1639G>A.ConclusionTo enhance the safety of at least 11 clinically significant drugs, the current study found that approximately one-fifth of the global population is at risk based on the CYP2C9*2 and *3 genotypes. Additionally, approximately one-third of the population is at risk when considering the combination of CYP2C9 and VKORC1 c.-1639G>A genotypes. Further studies are warranted to evaluate the clinical benefits of integrating PGx-based therapies in routine practice.